Understanding and awareness towards Hibah : a study among the staff in UiTM Puncak Alam / Fatin Aqilah Maskuri - Maskuri, Fatin Aqilah (Academy of Contemporary Islamic Studies (ACIS), 2018)
Nowadays, the existence of unclaimed property after the death of the owner of that property is keep increasing. Hibah is one of estate management planning in Islam which is not widely practiced by Muslims in this country. Most of Malaysian Muslims do not understand the concept of hibah because of inadequate knowledge plus they do not really expose with the implementation of hibah. Moreover, they are facing difficulties to whom they should refer to manage their property due to the lack of exposure of hibah practice by the institution that offer estate management planning. In fact, today there are many institutions that provide services for property management planning including hibah. Hence, this study will review on: 1) the level of knowledge on hibah, 2) the implementation of hibah and 3) the problems and difficulties faced in wealth management planning. This study used quantitative method and collected the data via questionnaire survey to achieve the objectives of the research. Based on the data from the respondents, it is found that the respondents do know about hibah and they will implement hibah to their heirs later in the future. Regarding the problems and difficulties, the respondents likely not having too much problems in wealth management planning.